2022
DOI: 10.1021/acs.iecr.2c01459
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Concentration and Temperature Distribution in a Berty Reactor for an Exothermic Reaction

Abstract: The Berty reactor is a continuously operated stirred tank reactor that is used in catalytic experiments to achieve gradientless conditions. Uniformity of the concentration profile has been confirmed through residence time measurements, but the temperature profiles originating from the heat of reaction have not been investigated yet. In this work, the profiles inside the reactor are investigated for the exothermic methanation of CO2 under typical operating conditions for kinetic measurements via Computational F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Typical results are presented in Figure 2a for a temperature of 340 °C, a pressure of 5 bar, and γ = 0.5. The comparison of the predicted and simulated He profile highlights that the Berty reactor behaves as an ideal CSTR, verified also by CFD simulations [58] and that the reactor model with its parameters is justified. Simulation results from generated models in this global uncertainty assessment (GUA) reveal a broad spread of possible concentration profiles, ranging from no activity for CH 4 formation to very high activity.…”
Section: Microkinetic Modelingsupporting
confidence: 54%
See 2 more Smart Citations
“…Typical results are presented in Figure 2a for a temperature of 340 °C, a pressure of 5 bar, and γ = 0.5. The comparison of the predicted and simulated He profile highlights that the Berty reactor behaves as an ideal CSTR, verified also by CFD simulations [58] and that the reactor model with its parameters is justified. Simulation results from generated models in this global uncertainty assessment (GUA) reveal a broad spread of possible concentration profiles, ranging from no activity for CH 4 formation to very high activity.…”
Section: Microkinetic Modelingsupporting
confidence: 54%
“…The maximum concentration of this overshoot does not exceed the maximum value from the stoichiometric cycle split ratio in Figure 1a. Recorded temperature variations above and below the catalyst basket are limited to ±1.5 K indicating isothermal behavior, which is supported by CFD simulations [58] . Temperature fluctuations can also be caused by the different thermal conductivity of the gas mixtures during periodic operation [5,13] …”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The blower wheel ensured a high internal recirculation of the gas. The same reactor design is used in several kinetic studies. ,, A detailed description and characterization can be found in the publication of Haumann et al Using computational fluid dynamics simulations of the methanation reaction in the same reactor, Anderson et al showed that a gradient-less operation can be ensured at high rotational speeds of the blower wheel and at elevated pressures. We validated this statement by blower wheel rotational speed and pressure variation measurements (cf., Section S1, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is a powerful method for investigating mixing patterns in this type of reactor concerning their hydrodynamic performances. 16,32,36–40 Ahmed et al 32 verified the CFD simulations using experimental data and mass balance calculations by a model with pressure drop assigned to the particle bed and basket grids for the CREC riser simulator and compared the mixing patterns of reactor designs with and without baffles. Cui et al 36 validated the CFD simulations, assuming the catalyst bed as a porous media zone.…”
Section: Introductionmentioning
confidence: 99%